A Discussion of the Treatment of People with an Intellectual Disability Across Healthcare and the Modernization of Learning Disability Nursing - Inglis, Pamela; Powell, Hazel; Ridley, Angela; McQueen, Sheila (Journal of Intellectual Disability - Diagnosis and Treatment, 2015)
Aims: A discussion of the treatment of people with an intellectual disability across healthcare and the modernisation of learning disability nursing. Background: Health inequalities are at the forefront of the collective mind of healthcare professionals and politicians, this paper explores why people with an intellectual disability have more health issues, die earlier and sometimes receive poor care, leading to unnecessary suffering and importantly, how this may change. Learning disability nursing has long been viewed as different and less valued, probably due to dual stigmatisation, or lack of understanding of specialist knowledge and skills required. This essential field of nursing is becoming a rare resource in our battle against health inequalities, yet internationally it is becoming recognised as crucial. Design: Discussion Paper. Data Sources: Literature and policy (1971 – 2012). Implications for Nursing: All nurses need to recognise their role in meeting the health care needs of people with an intellectual disability. Health care managers and commissioners should value the unique contribution of learning disability nurse in addressing health inequalities. Conclusion: Learning disabled people, their carers and professionals view the role of the learning disability nurse as central for effectively identifying and meeting health needs, reducing inequalities and barriers, supporting decisions around capacity, consent, best interests and advising and educating professionals. Recommendations for commissioning, nursing and services are made. Summary Statement: Why is this discussion paper needed? People with an intellectual disability have shorter life-spans and receive poor healthcare because of the barriers to good health developed in societies constructed by and for people without a disability. Internationally, the need for learning disability nurses, with their specific knowledge and skills, is being recognised in the battle against early and unnecessary deaths because of discrimination and health inequalities. Learning disability nurses and ‘Strengthening the Commitment’ lead on improving healthcare for learning disabled people and this paper raises the profile of this important health issue. What are the key findings? This discussion paper explores how most of the poor health experienced by people with an intellectual disability is about discriminating healthcare provision and crucially, not because the person has a disability. People with an intellectual disability have greater health needs than others and despite this, nonspecific health professionals often have scant understanding of their disability and health needs. Learning disability nursing as a vital resource has in recent years seen posts reducing in the NHS, with actual and commissioned numbers of registered learning disability nurses dropping. How should the findings be used to influence policy/practice/education/research? People with an intellectual disability and nonspecific staff often feel they are inadequately educated and lack appropriate skills for quality healthcare provision for learning disabled people; this has to change. Sir Johnathon Michael (2008) recommendation 1 advises that all health professionals be competent in supporting learning disabled people in a non-discriminatory way - universities and employers urgently need to adhere to this recommendation. Professionals, learning disabled people and carers state learning disability nurses are vital to acquiring human rights - increased international commissioning for learning disability nurses to enable quality healthcare, education and advice to professionals is pressing.